MEMBANGUN MANAJEMEN EKONOMI BERPRINSIP SYARIAH - Maksum (Al'Adalah, 2014)
In islamic perspective everything must be done, in a tidy manner true, orderly, regular, directed clear and settled to an end. The process must always followed well. Nothing is certainly not be done in not planned because it is a principle that major in Islamic beliefs. Rasulullah said in a hadith being narrated thabrani, the priest, “surely god loved one who, if do any work done in itqan (timely directed clear and settled)”.The clear work the steady, and transparent manner gotcha charity work which is loved by God. Actually, management in meaning regulate everything to do well quick, and it is been Sharia in Islamic Beliefs. Syariah management is the behavior associated with the values of faith and ketauhidan, every behavior one who engages in an activity based on tauhid with the value of, and expected behavior will be restrained and not occurring KKN behavior (corruption, collusion, and nepotism) because realized the supervision of the most high, which is god to record every charitable deeds both good and bad.This is different with the behavior in the management of conventional not at all related even in spite of tauhid values. Those who apply the management of conventional not feel the supervision that is attached, except only the supervision of the leader or a superior. Any activity in the management of Sharia, attempts to pious charity by perennial worth.